Sleepwalking, criminal behavior, and reliable scientific evidence : a guide for expert witnesses - Pressman, Mark R. (American Psychological Association, 2018)
"This book is an attempt to provide a method and knowledge for examining evidence and testimony that has a basis in reliable and sound sleep science. It attempts to provide both the proper scientific and forensic context for the expert witness. The chapters will lead the reader through the different types of scientific knowledge and forensic practices that need to be understood and that can be brought to bear on the evaluation of criminal cases, both for the prosecution and defense. Chapter one offers a brief introduction to sleep and sleep disorders, and Chapter two introduces essential forensic issues such as legal standards for admissibility of scientific evidence in court, the duty of the expert witness, and constraints put on expert witnesses. Chapter three presents basic information on parasomnias--the diagnostic category that includes sleepwalking and related disorders most often involved as a defense in criminal cases. Chapter four describes the use and abuse of polysomnography or sleep studies. Chapters five and six focus directly on the process of pretrial assessment and the gathering and presentation of direct and indirect evidence. Chapter seven includes detailed descriptions of criminal cases involving sleepwalking or sleep terror defenses for murder and attempted murder in the absence of alcohol or drugs. Chapter eight reviews the scientific evidence for a popular form of sleepwalking defense: the alcohol-induced sleepwalking or sexual-behavior-in-sleep defense. Chapter nine examines the validity and reliability of drug-related sleepwalking and sleep-driving defenses."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)